2020
DOI: 10.1177/0194599820931470
|View full text |Cite
|
Sign up to set email alerts
|

Cricopharyngeal Achalasia: Management and Associated Outcomes—A Scoping Review

Abstract: Objective There is little consensus regarding the efficacy and safety of treatment options for cricopharyngeal (CP) achalasia. The purpose of this scoping review is to assess the literature regarding the various treatments for this disease. Data Sources PubMed was searched for all articles addressing treatment of adult CP achalasia between January 1990 and June 2019. Review Methods In total, 351 peer-reviewed results were reviewed by 3 otolaryngologists for inclusion. After review of titles, abstracts, and ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
10
0
3
Order By: Relevance
“…The presence of a cricopharyngeal bar on video‐fluoroscopy is not uncommon in IBM, 25 which frequently leads to obstruction‐related dysphagia and increased risk for aspiration pneumonia 26 . This is not pathognomonic for IBM however, as a cricopharyngeal bar can be encountered in other inflammatory myopathies, inherited myopathies and with aging 27,28 . Nevertheless, recognition of this finding may result in earlier interventions to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a cricopharyngeal bar on video‐fluoroscopy is not uncommon in IBM, 25 which frequently leads to obstruction‐related dysphagia and increased risk for aspiration pneumonia 26 . This is not pathognomonic for IBM however, as a cricopharyngeal bar can be encountered in other inflammatory myopathies, inherited myopathies and with aging 27,28 . Nevertheless, recognition of this finding may result in earlier interventions to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…26 This is not pathognomonic for IBM however, as a cricopharyngeal bar can be encountered in other inflammatory myopathies, inherited myopathies and with aging. 27,28 Nevertheless, recognition of this finding may result in earlier interventions to improve outcomes. In our study, a cricopharyngeal bar was found in 64% of patients with dysphagia onset, which led to cricopharyngeal myotomy or balloon dilatation in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…CPA is a typical dysphagia associated with stroke [ 5 ]. Lateral medullary lesion has been identified as an independent predictor for CPA [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…CPA usually cause severe dysphagia, with serious complications which could lead to an increase in medical expenses and mortality, a decrease in quality of life, etc (Kocdor et al, 2016 ). Currently, balloon dilation is a regular treatment of post-stroke CPA (Dou et al, 2012 ; Dewan et al, 2020 ). Through repeated mechanical traction and dilation, balloon dilation can relax the cricopharyngeal muscle (CPM) and improve swallowing (Suntrup et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%